2003
DOI: 10.1007/s00497-003-0172-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytological investigation of male sterility in sorghum caused by a dominant mutation (Ms tc ) derived from tissue culture

Abstract: Male sterility mutations are an important tool in the investigation of anther and pollen development and for obtaining hybrid seeds in plant breeding. Cytological analysis of microsporo-and microgameto-genesis in sorghum plants with dominant mutation of male sterility (Ms tc ) derived from tissue culture has been carried out. Using substitution backcrosses, this mutation was introduced first into the nuclear background of the fertile sorghum line SK-723 and from this line into Volzhskoe-4w (V-4w). The mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The abortion of microspores of Yamian A was caused by delayed development of tapetum cells (Fig. S5 ) [ 16 ], which was different from the abortion methods summarized by previous studies that were caused by excessive hypertrophy or premature disintegration of tapetum cells; the activities of peroxidase and so on were related to the male sterility of Yamian A [ 57 ]. The source of the material and mitochondrial RAPD analysis indicated that the sterile cytoplasm of Yamian A was different from that of the existing Gossypium harknessii cytoplasmic male sterile line (Ha A) [ 58 ] and jin A [ 59 ] (Fig.…”
Section: Methodsmentioning
confidence: 95%
“…The abortion of microspores of Yamian A was caused by delayed development of tapetum cells (Fig. S5 ) [ 16 ], which was different from the abortion methods summarized by previous studies that were caused by excessive hypertrophy or premature disintegration of tapetum cells; the activities of peroxidase and so on were related to the male sterility of Yamian A [ 57 ]. The source of the material and mitochondrial RAPD analysis indicated that the sterile cytoplasm of Yamian A was different from that of the existing Gossypium harknessii cytoplasmic male sterile line (Ha A) [ 58 ] and jin A [ 59 ] (Fig.…”
Section: Methodsmentioning
confidence: 95%